Cysteine-Mediated Gene Expression and Characterization of the CmbR Regulon in Streptococcus pneumoniae - Afzal, Muhammad; Manzoor, Irfan; Kuipers, Oscar P.; Shafeeq, Sulman (Frontiers in Microbiology, 2016)
In this study, we investigated the transcriptomic response of Streptococcus pneumoniae D39 to cysteine. Transcriptome comparison of the D39 wild-type strain grown at a restricted concentration of cysteine (0.03 mM) to one grown at a high concentration of cysteine (50 mM) in chemically-define medium (CDM) revealed elevated expression of various genes/operons, i.e. spd-0150, metQ, spd-0431, metEF, gshT, spd-0618, fhs, tcyB, metB-csd, metA, spd-1898, yvdE, and cysK, likely to be involved in the transport and utilization of cysteine and/or methionine. Microarray-based data were further confirmed by quantitative RT-PCR. Promoter lacZ-fusion studies and quantitative RT-PCR data showed that the transcriptional regulator CmbR acts as a transcriptional repressor of spd-0150, metEF, gshT, spd-0618, tcyB, metA, and yvdE, putatively involved in cysteine uptake and utilization. The operator site of CmbR in the promoter regions of CmbR-regulated genes is predicted and confirmed by mutating or deleting CmbR operator sites from the promoter regions of these genes.